2022
DOI: 10.1017/jfm.2022.491
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pore scale and conjugate heat transfer on thermal convection in porous media

Abstract: The study of thermal convection in porous media is of both fundamental and practical interest. Typically, numerical studies have relied on the volume-averaged Darcy–Oberbeck–Boussinesq (DOB) equations, where convection dynamics are assumed to be controlled solely by the Rayleigh number (Ra). Nusselt numbers (Nu) from these models predict Nu–Ra scaling exponents of 0.9–0.95. However, experiments and direct numerical simulations (DNS) have suggested scaling exponents as low as 0.319. Recent findings for solutal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…When the thickness of the thermal boundary layer is comparable to the averaged pore length scale ( ), the transition from one regime to the other occurs. In addition to the porous structure and the Rayleigh number, in case of thermal convection, the boundary layer thickness and the heat transfer coefficient are determined also by the value of thermal conductivity of the solid and liquid phases [ 76 , 77 ].
Fig.
…”
Section: Rayleigh–bénard Convectionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the thickness of the thermal boundary layer is comparable to the averaged pore length scale ( ), the transition from one regime to the other occurs. In addition to the porous structure and the Rayleigh number, in case of thermal convection, the boundary layer thickness and the heat transfer coefficient are determined also by the value of thermal conductivity of the solid and liquid phases [ 76 , 77 ].
Fig.
…”
Section: Rayleigh–bénard Convectionmentioning
confidence: 99%
“…While in the two-dimensional case [ 54 , 62 ] this scaling sets in at , in three-dimensional flows [ 58 , 59 ] the ultimate state is expected to take place at , which is beyond the present numerical capabilities. Pore-scale simulations have revealed a more complex scenario, in which the heat/mass transfer is also influenced by porosity [ 30 , 31 ], Schmidt number and relative conductivity of fluid and solid phases [ 76 , 77 ]. These extensive numerical campaigns have led to the development of physics-based correlations for as a function of the flow parameters.…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…They observed that the scaling crossover occurs when the thickness of the thermal boundary layer is comparable to the averaged pore length scale. In addition to the porous structure and the Rayleigh number, in case of thermal convection, the boundary layer thickness and the heat transfer coefficient are determined also by the value of thermal conductivity of the solid and liquid phases (Korba & Li 2022; Zhong, Liu & Sun 2023).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Paknahad et al [26] studied metal foam at pore scale using a regularized collision operator for the thermal solver, but only steady-state conditions were considered. In another study, Korba and Li [27] investigated thermal convection and conjugate heat transfer in porous media and resolved the turbulent flow through direct numerical simulation.…”
Section: Introductionmentioning
confidence: 99%